Envolvimento dos receptores CysLT1 nas crises induzidas por pentilenotetrazol em camundongos, na permeabilidade da barreira hematoencefálica e na modulação da enzima na+,k+-ATPase em hipocampo - Lenz, Quéli Fernandes (2014)
Growing evidence has shown that leukotrienes are important contributors in the pathophysiology of several SNC inflammatory diseases where excitotoxicity is involved, including traumatic brain injury, encephalitis, Parkinson's disease, ischemia, epilepsy and neuropathic pain. However little is known about the molecular mechanism by which leukotrienes facilitate excitatory activity in the brain. Thus, in this study we investigated the effect of antagonists for cysteinyl leukotrienes receptors (CysLT) on PTZ-induced seizure in mice. Bay-u9973 (3 and 30 nmol), montelukast (0.03 and 0.3 μmol) and pranlukast (1 and 3 μmol), increased the latency to generalized seizures and decreased the mean amplitude of EEG recordings during seizures. LTD4 (0.2 and 2 pmol) reverted the anticonvulsant effect of montelukast (0.3 μmol). Montelukast (0.03 and 0.3 μmol) prevented PTZ-induced BBB disruption, an effect that was reversed by LTD4 (6 pmol). In addition, doses of LTD4 (0.2 and 2 pmol) which reversed the effect of montelukast in crisis did not alter the protective effect of montelukast on the barrier, dissociating the anticonvulsant of protective effect on BBB. The confocal microscopy analysis revealed that 1. PTZ increased the number of CD45+ and IgG cells in cerebral cortex, indicating BBB leakage with leukocyte infiltration; 2. while LTD4 (6 pmol) potentiated, montelukast decreased the effect of PTZ on leukocyte migration. Considering that increase levels of leukotrienes and decrease in Na+,K+-ATPase are common findings in several excitotoxic conditions, including epileptic seizures, we also investigated the effects of LTD4 on the activity of Na+,K+-ATPase activity in mice hippocampal slices. LTD4 10 and 100 nM decreases Na+,K+-ATPase activity alpha 2, 3 and alpha 1 subunits, respectively, in mice hippocampal slices. The inhibitory effect of LTD4 on Na+,K+-ATPase activity was not observed in hippocampal homogenates, indicating that it requires intact cells. Moreover, we showed that LTD4-induced decrease Na+,K+-ATPase activity was reversed by CysLT1R inverse agonis, montelukast (1 μM). In addition, we also showed that possibly the PKC activation pathway is involved in LTD4-induced decrease of Na+,K+-ATPase activity in mice hippocampal slices, since PKC inhibitor, GF 109203X (0,3 μM), prevent this effect. Finally, but not least important, we have demonstrated that animals injected with LTD4 (2 pmol/3 μL icv), there also occurs a decrease in Na+,K+-ATPase activity, corroborating our in vitro findings and confirming the biological importance of this work. In summary, we showed that CysLT1 receptor activation modulates hippocampal Na+,K+-ATPase activity in mice, suggesting a possible mechanism for the involvement of leukotrienes in several dosorders related with brain inflammation and hyperexcitability.